STUDI BIOEKIVALENSI AMSTUDI BIOEKIVALENSI AMOKSISILIN GENERIK DAN DAGANG MENGGUNAKAN MATRIKS URINOKSISILIN GENERIK DAN DAGANG MENGGUNAKAN MATRIKS URIN - Dwi Leboe; Elly Wahyudin; Tadjuddin Naid (Universitas Islam Negeri Alauddin Makassar, 2014)
Bioequivalence studies of amoxicillin which derived from generic drugs (OGB) had been done as a product test with branded amoxicillin as a comparison using urine matrix. The purpose of this study is to measure the bioavailability parameters based on 24 hours urine, so it is known as bioequivalent or bioinequivalent. Based on approach to cheap and quality generic drugs, and referring to the BPOM RI guidelines for bioequivalence, so this study using 12 healthy people aged 18 -21 years as a subject. The study design is the design crossed two-way (2 way) for 2 periods of treatment in two drug products, according to the selection of 24-hour urine matrix and determination of amoxicillin level by spectrophotometry UV Vis at wavelength of 273 nm, whereas the bioavailability parameters determined by using the cumulative profile of amoxicillin in the 24 hours urine and the rate of excretion. The results of the geometric mean and ratio CI 90% based on cumulative levels of amoxicillin were 104.67% and 117.65%, while based on the rate of amoxicillin excretion in 24 hours urine is 105.23% and 118.29%. All within the range 80-125% as a drug with a broad therapeutic index. Means that amoxicillin generic product (OGB) which had been studied is bioequivalet with the product branded amoxicillin.